2020
DOI: 10.3390/atoms8020014
|View full text |Cite
|
Sign up to set email alerts
|

Positron Processes in the Sun

Abstract: Positrons play a major role in the emission of solar gamma-rays at energies from a few hundred keV to >1 GeV. Although the processes leading to positron production in the solar atmosphere are well known, the origin of the underlying energetic particles that interact with the ambient particles is poorly understood. With the aim of understanding the full gamma-ray spectrum of the Sun, I review the key emission mechanisms that contribute to the observed gamma-ray spectrum, focusing on the ones involving positr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…For a long time, it was thought that only processes involving electrons contribute to the opacity of the Sun and the interstellar medium. However, positrons do exist in many regions of the Sun and the interstellar medium [51]. Therefore, it is necessary to consider positrons in calculations of opacity.…”
Section: Discussionmentioning
confidence: 99%
“…For a long time, it was thought that only processes involving electrons contribute to the opacity of the Sun and the interstellar medium. However, positrons do exist in many regions of the Sun and the interstellar medium [51]. Therefore, it is necessary to consider positrons in calculations of opacity.…”
Section: Discussionmentioning
confidence: 99%
“…SGREs >100 MeV are produced by >300 MeV protons precipitating from the solar corona into the solar chromosphere, where their interactions with the dense plasma layers create pions, which then decay into the observed >100 MeV gamma rays (e.g., Murphy et al 1987). The dominant source of >100 MeV gamma rays is neutral pion decay (e.g., Kafexhiu et al 2018;Gopalswamy 2020). Forrest et al (1985) first reported a clear detection of >40 MeV gamma rays that require pion production during the extended phase of the 1982 June 3 gamma-ray flare.…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that there are positrons present in the Sun [8] and in interstellar space, as indicated by the detection of the 0.511 MeV line from the center of the galaxy due to the annihilation of the positron and electron pairs [9,10]. Positrons are produced due to various processes: when two protons collide, during the formation of 3 He nuclei, the decay of radioactive nuclei, and the decay of positive pions to muons, which further decay into positrons [11].…”
Section: Introductionmentioning
confidence: 99%